EPIDEMIOLOGY OF BRUCELLOSIS OUTBREAKS – LITERATURE REVIEW - Urazayeva, Aisha; Urazayeva, Saltanat; Tussupkaliyeva, Kymbat; Tadevosyan, Artashes; Bekenov, Zhumabek (Revista Inclusiones, 2020)
The relevance of the present study lies in the extremely high prevalence of brucellosis, a disease of social and economic importance. The study presents the literature review on the prevalence of human brucellosis in the world. The scientific search was conducted in the Elibrary, Google Scholar, Pubmed, Web of Science, Scopus, and Medline databases; a 15-year period was regarded (2005 to 2019). 46 articles corresponded to the objectives of the study. The present work describes the incidence and prevalence of human brucellosis in different countries and continents, the epidemiological criteria for brucellosis, and its frequency and characteristics among children. Results of surveys of risk groups to assess the level of brucellosis awareness and of risky practices are given; outbreaks and cases among travelers are described; and special attention is paid to specific factors and conditions of human infection in different regions. The following conclusion is made: successful eradication of brucellosis is possible only with comprehensive programs of public health services and veterinary control combined with appropriate training programs for agricultural workers.